2018
DOI: 10.1186/s13063-018-2974-z
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injury clinical trial evaluating tranexamic acid in children (TIC-TOC): study protocol for a pilot randomized controlled trial

Abstract: BackgroundTrauma is the leading cause of morbidity and mortality in children in the United States. The antifibrinolytic drug tranexamic acid (TXA) improves survival in adults with traumatic hemorrhage, however, the drug has not been evaluated in a clinical trial in severely injured children. We designed the Traumatic Injury Clinical Trial Evaluating Tranexamic Acid in Children (TIC-TOC) trial to evaluate the feasibility of conducting a confirmatory clinical trial that evaluates the effects of TXA in children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…All-cause mortality was significantly reduced with TXA by 1.5%; the risk of death due to bleeding was significantly reduced by 0.8% and a reduction in bleeding deaths by one third, mainly through preventing exsanguination within the first 24 h [ 489 , 490 ]. Paediatric patients were not included in the CRASH-2 study; however, an ongoing study is investigating the use of TXA in children [ 491 ] and a study in children undergoing craniosynostosis surgery [ 492 , 493 ] administered an initial bolus of 15–30 mg/kg followed by 2−10 mg/kg/h. One retrospective study has suggested that TXA is of no benefit in patients with viscoelastic hyperfibrinolysis [ 494 ] and another found TXA to reduce multiple organ failure and mortality in severely injured shocked patients [ 495 ].…”
Section: Resultsmentioning
confidence: 99%
“…All-cause mortality was significantly reduced with TXA by 1.5%; the risk of death due to bleeding was significantly reduced by 0.8% and a reduction in bleeding deaths by one third, mainly through preventing exsanguination within the first 24 h [ 489 , 490 ]. Paediatric patients were not included in the CRASH-2 study; however, an ongoing study is investigating the use of TXA in children [ 491 ] and a study in children undergoing craniosynostosis surgery [ 492 , 493 ] administered an initial bolus of 15–30 mg/kg followed by 2−10 mg/kg/h. One retrospective study has suggested that TXA is of no benefit in patients with viscoelastic hyperfibrinolysis [ 494 ] and another found TXA to reduce multiple organ failure and mortality in severely injured shocked patients [ 495 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the study period, there were a total of 48 patients who were identified using the MTP order, 29 (60%) of whom received TXA in the course of their trauma management. The patients were predominantly male (34, 71%) with an overall median (IQR) age of 14 [7][8][9][10][11][12][13][14][15] years. Baseline characteristics between groups were similar (Table 1), except that patients who received TXA were significantly older (median [IQR]: 14 [12][13][14][15][16] vs 11 [4][5][6][7][8][9][10][11][12][13][14], P ¼ .001).…”
Section: Resultsmentioning
confidence: 99%
“…The patients were predominantly male (34, 71%) with an overall median (IQR) age of 14 [7][8][9][10][11][12][13][14][15] years. Baseline characteristics between groups were similar (Table 1), except that patients who received TXA were significantly older (median [IQR]: 14 [12][13][14][15][16] vs 11 [4][5][6][7][8][9][10][11][12][13][14], P ¼ .001). A majority of patients presented with major trauma based on ISS greater than 15, but there was no difference between groups in severity or type of trauma (penetrating vs blunt).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[6][7][8][9] Its use in pediatrics has been seen with scoliosis repair, congenital heart repair, and craniosynostosis repair, but has also been increasingly reported in pediatric trauma, such as in the Clinical Randomization of an Antifibrinolytic in Significant Hemorrhage (CRASH-2) trial, diffuse alveolar hemorrhage (DAH), and more recently with post-tonsillectomy hemorrhage. [1][2][3][4][5][6][7][8][9][10][11] As a result of broadening use with limited patient numbers actual dosing parameters are not well established, nor is the safety profile when used for these indications.…”
Section: Discussionmentioning
confidence: 99%